Teyvappulavar Tiruvaḷḷuvar iyaṟṟiya Tirukkuṟaḷ, Aṟattuppāl - Subrahmanya Sastri, P. S., 1890-1978 (SAMP early 20th-century Indian books project, 1939)
Commentary on the Aṟattuppāl part of Tirukkuṟaḷ, Tamil didactic work, by Tiruvaḷḷuvar.